2022
DOI: 10.3390/microorganisms10050848
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Combination Therapy for Treating Methicillin-Susceptible Staphylococcus aureus Bacteremia: A Systematic Literature Review and a Meta-Analysis

Abstract: Background: This meta-analysis aims to evaluate the effectiveness of combination therapy for treating MSSA bacteremia. Methods: We searched Ovid MEDLINE, EMBASE, Cochrane CENTRAL, and clinicaltrials.gov for studies including adults with MSSA bacteremia. The monotherapy group used a first-line antibiotic active against MSSA and the combination group used a first-line antibiotic plus additional antibiotic/s. The primary outcome was all-cause mortality. Secondary outcomes included persistent bacteremia, duration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…John Hopkins recommends prescribing daptomycin, linezolid, or ceftaroline for severe infections or those at high risk of MRSA [31]. Commonly used drug combinations for S. aureus treatment are vancomycin and ceftaroline, daptomycin and ceftaroline, and a combination of vancomycin, linezolid, daptomycin, clindamycin, TMP-SMX along with rifampicin [32,33]. It is essential for antibiotic consumption in combination therapy to be guided by physicians or clinicians to prevent the emergence of antibiotic resistance.…”
Section: Drug Resistance In S Aureus: An Emerging Challengementioning
confidence: 99%
“…John Hopkins recommends prescribing daptomycin, linezolid, or ceftaroline for severe infections or those at high risk of MRSA [31]. Commonly used drug combinations for S. aureus treatment are vancomycin and ceftaroline, daptomycin and ceftaroline, and a combination of vancomycin, linezolid, daptomycin, clindamycin, TMP-SMX along with rifampicin [32,33]. It is essential for antibiotic consumption in combination therapy to be guided by physicians or clinicians to prevent the emergence of antibiotic resistance.…”
Section: Drug Resistance In S Aureus: An Emerging Challengementioning
confidence: 99%
“…Notably, combination therapy did not add any advantage over cefazolin or oxacillin monotherapy in the management of MSSA infections. A recent meta-analysis of 12 studies found that combination therapy did not reduce significantly the mortality rate at day 30 (RR 0.92; 95%CI 0.70–1.20), at day 90 (RR 0.89; 95%CI 0.74–1.06), or at any time (RR 0.91; 95%CI 0.76–1.08) in the treatment of MSSA bacteremia compared to monotherapy [ 27 ]. Furthermore, combination therapy was associated with a significantly higher risk of AEs (including nephrotoxicity) (RR 1.74; 95%CI 1.31–2.31; p < 0.001).…”
Section: Targeted Treatment Of Infections Caused By Staphyl...mentioning
confidence: 99%
“…2,3 Combination antibiotic salvage regimens for persistent MSSAB may help achieve bloodstream clearance faster, limit complications, and improve outcomes. 4,5 Few antibiotic salvage regimens exist for persistent MSSAB, and data are limited to case reports and case series to describe their effectiveness and safety. [5][6][7][8][9][10][11][12][13] Ertapenem plus cefazolin or an ASP has been predominately described, but identifying alternative carbapenem-sparing options is consistent with antibiotic stewardship efforts and may decrease the risk of antibiotic-associated Clostridioides difficile infection (CDI).…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Few antibiotic salvage regimens exist for persistent MSSAB, and data are limited to case reports and case series to describe their effectiveness and safety. [5][6][7][8][9][10][11][12][13] Ertapenem plus cefazolin or an ASP has been predominately described, but identifying alternative carbapenem-sparing options is consistent with antibiotic stewardship efforts and may decrease the risk of antibiotic-associated Clostridioides difficile infection (CDI). [14][15][16] Daptomycin is a lipopeptide antibiotic with activity against only gram-positive bacteria and has been shown to be effective in combination with a beta-lactam (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation